2017
DOI: 10.1038/s41598-017-03792-9
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 attenuates blast traumatic brain injury induced cognitive impairments, losses of synaptophysin and in vitro TBI-induced hippocampal cellular degeneration

Abstract: Mild blast traumatic brain injury (B-TBI) induced lasting cognitive impairments in novel object recognition and less severe deficits in Y-maze behaviors. B-TBI significantly reduced the levels of synaptophysin (SYP) protein staining in cortical (CTX) and hippocampal (HIPP) tissues. Treatment with exendin-4 (Ex-4) delivered by subcutaneous micro-osmotic pumps 48 hours prior to or 2 hours immediately after B-TBI prevented the induction of both cognitive deficits and B-TBI induced changes in SYP staining. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 77 publications
3
26
1
1
Order By: Relevance
“…Previous experiments involving our model of blast injury, at the same peak over-pressure, have yielded cognitive and behavioral changes in blast exposed mice similar to that TBI in humans at both acute and chronic timepoints, such as deficits in spatial and recognition memory and increased anxiety-like behavior 27,28 . One previous study also noted significant neurodegeneration within the neurons of the cortex and hippocampus at 3 days post-injury via FluoroJade B staining 29 .…”
mentioning
confidence: 79%
“…Previous experiments involving our model of blast injury, at the same peak over-pressure, have yielded cognitive and behavioral changes in blast exposed mice similar to that TBI in humans at both acute and chronic timepoints, such as deficits in spatial and recognition memory and increased anxiety-like behavior 27,28 . One previous study also noted significant neurodegeneration within the neurons of the cortex and hippocampus at 3 days post-injury via FluoroJade B staining 29 .…”
mentioning
confidence: 79%
“…Exendin-4 is an agonist of the glucagon-like peptide-1 receptor, which is currently prescribed for the treatment of type 2 diabetes and obesity 78 , 79 . However, several studies have also found its neuroprotective abilities in various models of neurological disorders 21 , 22 , 80 including a mouse model of blast-TBI 81 , 82 . In the current study, protective effects were shown in Exendin-4 treated rats with TBI at both 24 h and 6 weeks with similar effects to L-Carnitine on the cortex tissue and ameliorated neurological dysfunction and oxidative stress markers after the traumatic force.…”
Section: Discussionmentioning
confidence: 99%
“…These methods have been described previously. [25][26][27][28][29] Elevated plus maze Anxiety level was assessed using the elevated plus maze for ICR mice 8 weeks following the final closed head injury. The apparatus consisted of two open arms and two closed arms which were enclosed on all sides with the roof open (30 x 15 x 5 cm).…”
Section: Mtbi and Transcription Factor Modulation 1911mentioning
confidence: 99%